2011
DOI: 10.5402/2011/648703
|View full text |Cite
|
Sign up to set email alerts
|

Pericarditis Revealing Large Vessel Vasculitis

Abstract: Large vessels vasculitis and more specifically, Giant cell arteritis, is characterized by increased inflammatory markers, headaches and altered clinical status. Diagnosis is confirmed by biopsy of temporal arteries showing the presence of granuloma and vasculitis. We hereby report the case of a patient presenting initially as pericarditis and revealing large vessel vasculitis using FDG-PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Our study showed a significant interaction between GCA, pericarditis, and younger age (age < 70 years). These findings correspond well with most case reports and case series previously published on the subject . However, several articles have reported cases of adults age > 70 years with simultaneous presentations of both GCA and pericarditis, which usually regressed after corticosteroid treatment .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed a significant interaction between GCA, pericarditis, and younger age (age < 70 years). These findings correspond well with most case reports and case series previously published on the subject . However, several articles have reported cases of adults age > 70 years with simultaneous presentations of both GCA and pericarditis, which usually regressed after corticosteroid treatment .…”
Section: Discussionsupporting
confidence: 91%
“…These findings correspond well with most case reports and case series previously published on the subject. 8,9,19,[28][29][30][31] However, several articles have reported cases of adults age > 70 years with simultaneous presentations of both GCA and pericarditis, which usually regressed after corticosteroid treatment. 12,32-36 A Spanish case report described a 76-year-old female patient with pectoral girdle pain and a pleural effusion on x-ray who was eventually diagnosed with polymyalgia rheumatica (PMR) accompanied by pleuropericarditis and whose high levels of CA-125 indicated serosal involvement, rather than malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Pericarditis has also been reported [94]. However a recent large population-based cohort study in the UK analysing data on patients with GCA and/or PMR, showed that they were not at an increased risk of coronary diseases (stable angina, unstable angina, myocardial infarction, unheralded coronary death) and cardiac diseases, (heart failure and cardiac arrest) in comparison to age matched controls, regardless of PMR/GCA duration [80].…”
Section: The Cardiovascular Systemmentioning
confidence: 99%
“…Constrictive or effusive constrictive pericarditis, an uncommon complication of chemotherapy, can present with mild and diffuse pericardial FDG-uptake [ 94 ]. Additionally, pericarditis associated with increased metabolism of the wall of the large vessels like the thoracic or abdominal aorta can be caused by underlying vasculitis [ 98 , 99 ].…”
Section: Pericarditismentioning
confidence: 99%